The Influence of Ownership Structure, Business Risk, Growth Opportunity on Dividend Policy - Mendy, Egha Zanitha; Wenten, I Ketut (Formosa Journal of Sustainable Research, 2024)
The aim of this research is to determine the effect of Ownership Structure, Business Risk and Growth Opportunity on Dividend Policy in Consumer Companies listed on the Indonesia Stock Exchange in 2017 – 2022. Through the purposive sampling method, samples were collected from 36 companies for 6 years for research puproses. By utilizing Microsoft Excel and Eview 9 application software, the analysis process for this research involves panel data regression analysis. According to research, dividend policy is influenced by ownership structure and business risk and growth opportunity. Share ownership structure has no effect on Dividen Policy, while business risk partially has an effect on Dividend Policy and Growth Opportunity has no effect on dividend policy